English Bachelor Degree as Symbolic Capital - Nurhaliza, Anita Lucy; Widyastuti, Linda; iasya, Lubna; Kurniadiansyah, Meytha Dwi; Pangesti, Nesa Riska (Universitas PGRI Adi Buana Surabaya, 2026)
This study explores the symbolic function of an English Education bachelor's degree among working adults in Indonesia, particularly how it operates as a form of symbolic capital within the framework of Pierre Bourdieu's theory. Through a qualitative method using thematic analysis of in-depth interviews with working students, the research investigates their motivations, experiences of fatigue, learning focus, and perceived competence development. Findings reveal that the primary motivation for pursuing the degree is symbolic recognition rather than language mastery. While participants hoped to gain legitimacy and upward mobility, they often experienced cognitive exhaustion, declining motivation, and superficial learning engagement. Furthermore, the symbolic value of the degree simultaneously empowered and burdened their identity, triggering both pride and pressure. The study concludes that the pursuit of symbolic capital in higher education can compromise pedagogical and psychological outcomes if not accompanied by institutional support. These findings suggest the need for more inclusive and responsive academic policies that consider the unique challenges of adult learners.